Komunikasi Interpersonal Pada Relawan di Markas P4GN Kabupaten Sukoharjo - Pipit Nopiyanti (Concept: Journal of Social Humanities and Education, 2024)
Interpersonal communication is the ongoing communication between two or more individuals that can take place face-to-face and exchange information. The method in this research is a qualitative method. The subject of this study is the P4GN Volunteers Headquarters of Sukoharjo district. The results of this research are interpersonal communication in six volunteers at P4-GN Headquarter of Sukeharjo District. It really happens based on aspects of Joseph A Devito (2011), i.e. there is openness, there is empathy, there has been a positive attitude, there was an attitude of mutual help and there is equality.